The Influence of Product Innovation and Pricing on Purchasing Decisions at Rotte Bakery Bukit Barisan Pekanbaru - Mandataris; Mardalia; Safitri, Syofiatul; Othman, Lie (Formosa Journal of Multidisciplinary Research, 2024)
This research aims to determine the influence of product innovation and pricing on purchasing decisions at Rotte Bakery Bukit Barisan Pekanbaru. This research is quantitative research with a population and sample of 100 respondents. The data sources for this research were obtained from secondary and primary data. Collection and research use observation methods and distributing questionnaires. The instrument used was a questionnaire provided by researchers to assess using rating scale guidelines. The data obtained was processed then by carrying out a linearity test. The data analysis technique uses Statistical Program for Social Science (SPSS) version 23.0 analysis and hypothesis testing using the product moment correlation technique. The research results concluded that product innovation and pricing have a significant influence on purchasing decisions at Rotte Bakery Bukit Barisan Pekanbaru.